Seasonal changes and relationships between aerobic capacity, heart rate variability and iron status in junior cross-country skiers - Kuorelahti, Titta (2021)
Over the years, athlete monitoring has become a standard practice in helping athletes reach their peak performance. The several purposes for athlete monitoring include determining training adaptations and finding the balance between training and recovery. In endurance sports, where both training volume and intensity are relatively high, the monitoring of training is especially important to help maximize performance while ensuring sufficient rest and recovery. Maximal oxygen uptake (VO2max) is a widely used variable in estimating aerobic capacity while monitoring of recovery is a more complex process. There are several ways to define recovery status, including detecting changes in heart rate variability (HRV) and body iron status, which are very different but both commonly used measures among endurance athletes. The purpose of this study was to examine how aerobic fitness and recovery vary in junior female cross-country skiers before and after six-months long training season and to detect the relationships between aerobic capacity, HRV and iron status.